Analysis of Agricultural Waste Utilization as Biogas, Renewable Energy Management, and Compost Processing on Energy Efficiency in Bandung - Indriyani, Indriyani; Silamat, Eddy; Nugroho, Budi Sulistiyo; Annasit, Annasit; Hamid, Farid Alfalaki (Westscience Press, 2025)
The increasing need for energy efficiency and sustainable waste management has driven the exploration of agricultural waste utilization in urban settings. This study analyzes the role of agricultural waste in biogas production, renewable energy management, and compost processing to enhance energy efficiency in Bandung City. Using a quantitative approach, data were collected from 40 respondents through a structured questionnaire with a 5-point Likert scale. The findings reveal that biogas production, renewable energy management, and compost processing significantly contribute to energy efficiency, with renewable energy management having the most substantial impact. The study underscores the importance of integrated agricultural waste management in achieving urban sustainability and provides actionable insights for policymakers and stakeholders to scale these practices.